A 10-year prospectus for mathematical epidemiology - Orr, Mark; Mortveit, Henning S.; Lebiere, Christian; Pirolli, Pete (Frontiers in Psychology, 2023)
There is little significant work at the intersection of mathematical and computational epidemiology and detailed psychological processes, representations and mechanisms. This is true despite general agreement in the scientific community and the general public that human behavior--in its seemingly infinite variation and heterogeneity, susceptibility to bias, context and habit--is an integral if not fundamental component of what drives the dynamics of infectious disease. The COVID-19 pandemic serves as a close and poignant reminder. We offer a ten-year prospectus of kinds that centers around an unprecedented scientific approach: the integration of detailed psychological models into rigorous mathematical and computational epidemiological frameworks in a way that pushes the boundaries of both psychological science and population models of behavior.